Opera latina: une base de données sur internet - Denooz, Joseph (Euphrosyne, 2004)
Abstract Since 1961 the Laboratory for statistical analysis of ancient languages (LASLA) at the University of Liege has recorded a high number of ancient Latin texts in a computer format. For each of the approximately 1,800,000 words of the corpus lexicological, morphological and syntactical information has been entered. The complete data bank is now accessible through the Internet: an inquiry software package makes it possible for any researcher to look up all occurrences of a specific language feature either in the whole corpus or in the works of a given writer. Research can be done either on a lexis item, or on a type of subordination, or again on the basis of morphological features. The system, which still has to be further developed, is available for anyone who files a request.